Corrosion behavior of electro-deposited nickel aluminum composite coating on the stainless steel 316L - Nawal Mohammed Dawood, Dr.; Talib Abdulameer Jasim, Eng.; Zaid Falah Sharbah, Eng. (International Journal of Engineering and Technology, 2019)
The characterization of aluminum particulates charging in a coating cell on the morphology and corrosion behavior of nickel aluminum composite coating by an electro-chemical co-deposition coating were evaluated. The aluminum reinforced nickel matrix composite coatings were co-deposited on Austenitic Stainless Steel (316 L) work pieces by a nickel-ion electrolytic solution firmly postponed with -10 µm max. diameter aluminum particulates. The extreme limit of codeposited aluminum can be occurred at a particulate gratified of 50 g/l in cell, a current density of 4.5 A/dm2, a PH of 4.0 – 4.1, and a circulation rate of 400 rpm.Entirely codeposited specimens were heat treated under vacuum atmosphere for five hours at 950 °C prior to Potentiostatic testing. Throughout heat treatment, coating morphological development was initiated to occur by the exothermic reaction nickel +aluminum = nickel aluminum.Surface morphology was inspected by scanning electron microscopy(SEM) and X-ray diffraction (XRD) and atomic absorption. Furthermore, The electrochemical enactment of the coatings was considered by Potentiostatic test in 3.5wt.% NaCl. It was originate that, combination of aluminum particulates in nickel matrix sophisticated the nickel grains coatings. Though , polarization curves raised to negative potentials and the rate of corrosion is reduced.